2021
DOI: 10.1017/cts.2021.875
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and translational research workforce education survey identifies needs of faculty and staff

Abstract: Developing the translational research workforce is a goal established by the National Center for Advancing Translational Science for its network of Clinical and Translational Science Award Program hubs. We surveyed faculty and research staff at our institution about their needs and preferences, utilization of existing trainings, and barriers and facilitators to research training. A total of 545 (21.9%) faculty and staff responded to the survey and rated grant development, research project development, and prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Institutions that offer onsite trainings, such as lunch and learns and symposia have reported varying attendance to these events, particularly post-COVID. Time constraints and flexible schedules often hinder CRC attendance at these events [ 20 , 25 ]. Addressing these concerns led to the development of the TWD Catalog, a collaborative effort between the Georgia CTSA and the University of Southern California-CTSI.…”
Section: Discussionmentioning
confidence: 99%
“…Institutions that offer onsite trainings, such as lunch and learns and symposia have reported varying attendance to these events, particularly post-COVID. Time constraints and flexible schedules often hinder CRC attendance at these events [ 20 , 25 ]. Addressing these concerns led to the development of the TWD Catalog, a collaborative effort between the Georgia CTSA and the University of Southern California-CTSI.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative analysis of open-ended text box responses was performed by two researchers with qualitative training. Analysis was performed by two female analysts trained in qualitative methods 19 , 20 using a general inductive approach and thematic analysis. Comments were read multiple times through an iterative process to identify relevant categories related to the attitudes and barriers to research careers.…”
Section: Methodsmentioning
confidence: 99%
“…We determined that potential new site investigators would benefit from a structured training program; however, any program would need to include sufficient protected time to develop the expertise to be effective site investigators and establish a successful clinical trial portfolio. Reinforcing this notion were the results from a recent research education needs-and-utilization survey where faculty at our institution identified time as a primary barrier to engaging in research training and development activities [ 9 ].…”
Section: Introductionmentioning
confidence: 96%